Risk cost analysis in Malay heritage conservation project - Mohd Nawi, Nurul Hadirah; Che Haron, Roziha; Kamaruddin, Zumahiran (Malaysian Institute Of Planners, 2020)
Risks in conservation projects are believed to be different from risks in new building projects. There are different methods and processes that need to be adopted in order to handle a conservation heritage project. Heritage projects form a valuable inheritance with sentimental values that tell a certain history, culture or tradition which needs to be preserved. Nevertheless, many have reported that conservation projects frequently suffer failures in meeting the delivery goals of time, quality and budget, which lead to contractual disputes during the postcontract stages of a conservation project. Conservation work is riskier due to the inclusion of many activities such as preservation, restoration, and refurbishment. Thus, this research aims to identify the risk cost analysis in carrying out conservation projects through conducting semi-structured interviews and using the survey research method. The objectives are to highlight the importance of conserving Malay heritage and identify risk affecting cost of conserving heritage buildings. This research applied strategy survey through semi-structured interview and questionnaire survey. It was found that project risk consists of hidden works and uncertainties is the highest among other risk categories. The outcome of this research is considered to be significant and relevant as it contributes towards the conservation sector by minimising the risk of cost analysis taken on conservation projects by the project team involved.